Land use decision-making on residential plots in Fingo Village, Makhanda (Grahamstown), South Africa - Memela, Sinenhlanhla (Rhodes University, Faculty of Science, Department of Geography)
This study seeks to understand land use decision-making dynamics on large residential plots in Fingo Village, Makhanda (Grahamstown). Fingo Village was selected as a study area because it is one of the poorest urban settings in South Africa where urban poverty is observed alongside access to land. A dominant economic perspective not only suggests that land use decisions are motivated by economic motives, but also implies that access to land would enable people to generate income from its use to improve their livelihoods. This study argues against an uncritical embrace of this assumption. Lefebvre's production of space thesis provides a holistic understanding of the factors involved in the making of land use decisions. The focus of this study is on the dialectic process in the spatial triad"“ spatial practice, representational space and representations of space. This involved the reading of government policies and legislation together with local lived experiences to gain an understanding of the particular spatial practices seen in Fingo Village. Snowball and convenience sampling were used to select 36 household plots in Fingo Village. Primary data was gathered by means of semi-structured interviews and participatory mapping while additional information was sourced from secondary sources and desktop analysis. The findings of the study show that there is no uniform pattern of land use and success. Different land use activities found on the selected residential plots, including the main house, backyard flat or flats, spaza shops, a funeral parlour, livestock keeping, cultural use (a kraal for ancestral worship) and food gardening. These activities are motivated by residents' perceptions and attitudes towards their spaces, as well as the value and meaning they attach to the land which is not limited to economic factors, but is also influenced by socio-cultural, political and biophysical considerations. Although some spatial practices are prohibited by the government, they are important to the residents. Other participants fail to use the land as would be expected by a conventional economic perspective, due to spatial conflict relating to different interests as a result of collective land ownership and the failure of municipalities to enforce policies and regulations. The fact that numerous factors influence households' land use decisions means that access to land does not always directly translate into economic benefits. It is all about what people think or do about their land, as well as what the state lays out in terms of policy and legislation, that will influence whether those people with large plots of land will 'prosper' or not.
Keywords: Land use -- South Africa -- Makhanda Decision making; Land use, Urban -- South Africa -- Makhanda Decision making; Residential real estate -- South Africa -- Makhanda; Urban ecology (Sociology) -- South Africa -- Makhanda; Urban gardening -- South Africa -- Makhanda; Urban livestock production systems -- South Africa -- Makhanda